F. I. Tyutchev as a singer of nature and a representative of Russian cosmism - Karako, Piotr S. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article reveals the content of the cosmic expression of F. I. Tyutchev’s poetry. It manifests itself when he describes the nature of the Earth and its beauty. The Russian poet portrays nature as a form of cosmo-earthly existence. The philosophical foundation of his poetry, and cosmism, is pantheism. He recognises the presence of an immaterial factor – the feminine shadow, which determines the direction of the cosmic process. Attention is drawn to the poet’s fixation of the presence of discord between man and nature and the need to overcome it. The conclusion is drawn about the involvement of F. I. Tyutchev in the literary and artistic branch of Russian cosmism and its influence on the formation and development of space ideas among a number of representatives of Russian science and culture.
Keywords: nature; Earth; Sun; Moon; stars; sky; pantheism; symbolism; beauty; aesthetics of nature; feminine shadow; chaos; «thinking reed»; cosmic process; cosmism; Russian cosmism